Immediate effect of muscle energy technique versus passive stretching for upper trapezius muscle on neck pain - Ray, Mansi; Desai, Roopa (International Journal of Research in Orthopaedics, 2020)
Background: Neck pain is a common musculoskeletal problem in the General population. Upper trapezius is a superficial postural muscle that tends to get shortened due to overuse activity which causes neck pain and reduces neck mobility. The aim of this study was to compare the immediate effect of Muscle energy technique (MET) and passive stretching of upper trapezius muscle in neck pain patients. Methods: An experimental study was undertaken during period from March 2017 to March 2018. 358 participants with Neck pain were included in this study. Participants were divided in two groups: Group A received Hot pack and MET for upper Trapezius. Group B received Hot pack and Passive stretching for upper trapezius. Visual analogue scale (VAS) at end range of motion (ROM), same cervical side flexion and opposite side cervical rotation by goniometer and tape were taken as outcome measures. Participants were assessed prior to the treatment, immediately after the treatment and post 24 hours to see the carry over treatment. Results: Mann Whitney U test showed that VAS at end range of motion, opposite side cervical rotation and same side cervical side flexion had significant improvement in MET group as compared to passive stretching group (p<0.0001). Carry over effect was less significant with p<0.0001. Conclusions: A single session of MET for upper trapezius muscle reduced the pain intensity (VAS) and increased the cervical rotation and cervical side flexion.